Make time for you (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. If you've been feeling stressed out, anxious, or overwhelmed lately, you're not alone. Today's fast-paced, high-demand world requires us to manage so much and all at once. But, with a little tweak to your daily routine, you can more easily deal with what's being thrown at you. You can calm down, slow down, and de-stress by making more time for yourself. That's right, make time for yourself. Sounds simple, but how do we actually take a step back from our busy lives and practice self-care? Learning Objectives Learn how saying no can open up time for important self-care Learn meditating even for just a few minutes a day can have great benefits Learn how physical activity enables positive mood Learn how a good sleep pattern contributes to a calm mind.